2005
DOI: 10.1001/archsurg.140.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Scoring in Colorectal Cancer Liver Metastases

Abstract: Hypothesis: A prognostic scoring system for colorectal cancer liver metastases that is derived from unselected patients referred for hepatic resection would improve the applicability and increase the accuracy of prognostication. Design: Retrospective analysis of prospectively documented data; validation against an unrelated cohort from another institution. The median follow-up was 16.4 months (95% confidence interval, 15.0-17.8 months) (original cohort). Setting: Two tertiary referral centers at unrelated univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 42 publications
0
89
1
1
Order By: Relevance
“…51 Albumin was previously found to predict poor outcome both following resection of primary CRC 52 and in patients with metastatic disease. 53,54 The current study is the first to confirm that serum albumin is also an independent risk factor for poor outcome following CLM resection, though this prognostic value was inferior to that of the neutrophil count. Serum albumin was previously demonstrated to predict poor long-term outcome following cancer resection independently of CRP and has subsequently been combined with CRP to produce prognostic inflammatory scores validated in varied maligancies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…51 Albumin was previously found to predict poor outcome both following resection of primary CRC 52 and in patients with metastatic disease. 53,54 The current study is the first to confirm that serum albumin is also an independent risk factor for poor outcome following CLM resection, though this prognostic value was inferior to that of the neutrophil count. Serum albumin was previously demonstrated to predict poor long-term outcome following cancer resection independently of CRP and has subsequently been combined with CRP to produce prognostic inflammatory scores validated in varied maligancies.…”
Section: Discussionmentioning
confidence: 59%
“…55,56 In summary, the results of this study confirm that systemic inflammatory biomarkers, routinely available preoperatively, independently predict long-term survival following resection of CLM. As demonstrated here and elsewhere 14,[30][31][32]53,54 merging of inflammatory indices with existing prognostic scoring systems may enable further refinement of patient prognosis, so guiding allocation of existing therapeutic modalities.…”
Section: Discussionmentioning
confidence: 70%
“…The most cited factor was the number of liver metastases, identified by 15 different studies 11,20,[32][33][34][35][36][37]39,40,[42][43][44]46,47 as a negative prognostic factor. Only four studies 38,41,45,48 did not present it as a negative prognostic factor of survival after resection of CRLM.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…11,20,32,33,[35][36][37]39,42,[44][45][46] Nevertheless, six studies 34,38,40,41,47,48 concluded that regional lymph node metastases of primary tumor was not a significant prognostic factor for survival. This fact was supported by other studies not included in the analysis.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In the past, several clinical risk scores for the outcome of patients with CRLM have been published [7,[17][18][19][20][21][22][23][24][25]. In 1999, Fong et al described the most widely used CRS [19].…”
Section: Stratification By Clinical Risk Scorementioning
confidence: 99%